2021
DOI: 10.1111/1467-9566.13383
|View full text |Cite
|
Sign up to set email alerts
|

Sitting as a moral practice: Older adults’ accounts from qualitative interviews on sedentary behaviours

Abstract: Amidst public health campaigns urging people to sit less as well as being more physically active, this paper investigates how older adults make sense of their sedentary behaviour. Using an accounts framework focusing on how people rationalise their sitting practices, we analysed data from 44 qualitative interviews with older adults. All interviewees had received information about sedentary behaviour and health, visual feedback on their own objectively measured sitting over a week and guidance on sitting less. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…These are unique ndings and provide an important contribution to our understanding of the relationship between different domains and types of sitting behavior and MWB. Although there is limited research focusing on this relationship, the ndings are consistent with previous studies showing a differential effect of active and passive sedentary behaviors on mental well-being (19,25), and others who made a distinction between 'good' and 'bad' sitting (40). The current ndings are also consistent with research focusing on mental ill-health, and speci cally depression, that have highlighted a bene cial association between active sedentary behavior and reduced risk of depression, and a more negative association with passive sedentary behaviour (41).…”
Section: Discussionsupporting
confidence: 87%
“…These are unique ndings and provide an important contribution to our understanding of the relationship between different domains and types of sitting behavior and MWB. Although there is limited research focusing on this relationship, the ndings are consistent with previous studies showing a differential effect of active and passive sedentary behaviors on mental well-being (19,25), and others who made a distinction between 'good' and 'bad' sitting (40). The current ndings are also consistent with research focusing on mental ill-health, and speci cally depression, that have highlighted a bene cial association between active sedentary behavior and reduced risk of depression, and a more negative association with passive sedentary behaviour (41).…”
Section: Discussionsupporting
confidence: 87%
“…Educational programs alone aimed at disseminating knowledge on the negative health effects of sedentary behaviours may not be helpful to target cognitive dissonance as most older adults are aware that too much sitting can be harmful. Our study and the Palmer et al study (34) found older adults understood the negative effects of sedentary behaviours but believed that their sitting was different. Lui and colleagues published a comprehensive review of the international literature on age-friendly communities (42).…”
Section: Discussionsupporting
confidence: 46%
“…Similarly, Palmer et al 2020 found older adults moralize sitting by distinguishing different (active/'busy'/worthwhile versus passive/'not busy') types of sitting (34). The creation of "good" versus "bad" sedentary behaviours allows older adults to set themselves apart from other individuals whose sedentary behaviours may be considered deviant (e.g., lazy couch potato) (34). Like other public health information such as smoking, diet, and medical screening, participants in our study may be experiencing cognitive dissonance (35).…”
Section: Discussionmentioning
confidence: 99%
“…This categorization allows them to retain autonomy over their health decisions and differentiate themselves from perceived sedentary individuals. The findings of Palmer and colleagues' study [54] illuminate the complexity of older adults' views of SB and highlight the need to challenge ageist stereotypes and promote a comprehensive understanding of physical activity and SB in the context of aging.…”
Section: Definition and Shaping Perspectives On Sedentary Behaviormentioning
confidence: 89%
“…In a study by Palmer and colleagues [54], expressed sedentary habits using phrases such as "couch potato" to distinguish the sedentary and passive behaviors portrayed in the media from their own sedentary habits. This finding underscores the importance of distinguishing between passive and mentally active forms of SB in research [10][11][12].…”
Section: Definition and Shaping Perspectives On Sedentary Behaviormentioning
confidence: 99%